147k views
0 votes
Calcule o valor de x nas equações literais: a) 5x – a = x+ 5a b) 4x + 3a = 3x+ 5 c) 2 ( 3x -a ) – 4 ( x- a ) = 3 ( x + a ) d) 2x/5 - (x-2a)/3 = a/2 Resolva as equações fracionárias: a) 3/x + 5/(x+2) = 0 , U = R - {0,-2} b) 7/(x-2) = 5/x , U = R - {0,2} c) 2/(x-3) - 4x/(x²-9) = 7/(x+3) , U = R - {-3,3}

User Boojum
by
4.7k points

1 Answer

4 votes

Answer:

1) a)
x = (3)/(2)\cdot a, b)
x = 5-3\cdot a, c)
x = -a, d)
x = (5)/(2)\cdot a

2) a)
x = -(3)/(4), b)
x = -5, c)
x = 3

Explanation:

1) a)
5\cdot x - a = x + 5\cdot a


5\cdot x - x = 5\cdot a + a


4\cdot x = 6\cdot a


x = (3)/(2)\cdot a

b)
4\cdot x + 3\cdot a = 3\cdot x + 5


4\cdot x - 3\cdot x = 5 - 3\cdot a


x = 5-3\cdot a

c)
2\cdot (3\cdot x - a) - 4\cdot (x-a) = 3\cdot (x+a)


6\cdot x -2\cdot a -4\cdot x +4\cdot a = 3\cdot x +3\cdot a


6\cdot x -4\cdot x -3\cdot x = 3\cdot a -4\cdot a +2\cdot a


-x = a


x = -a

d)
(2\cdot x)/(5) - (x-2\cdot a)/(3) = (a)/(2)


(6\cdot x-5\cdot (x-2\cdot a))/(15) = (a)/(2)


(6\cdot x - 5\cdot x+10\cdot a)/(15) = (a)/(2)


2\cdot (x+10\cdot a) = 15 \cdot a


2\cdot x = 5\cdot a


x = (5)/(2)\cdot a

2) a)
(3)/(x) + (5)/(x+2) = 0


(3\cdot (x+2)+5\cdot x)/(x\cdot (x+2)) = 0


3\cdot (x+2) + 5\cdot x = 0


3\cdot x +6 +5\cdot x = 0


8\cdot x = - 6


x = -(3)/(4)

b)
(7)/(x-2) = (5)/(x)


7\cdot x = 5\cdot (x-2)


7\cdot x = 5\cdot x -10


2\cdot x = -10


x = -5

c)
(2)/(x-3)-(4\cdot x)/(x^(2)-9) = (7)/(x+3)


(2)/(x-3) - (4\cdot x)/((x+3)\cdot (x-3)) = (7)/(x+3)


(1)/(x-3)\cdot \left(2-(4\cdot x)/(x+3) \right) = (7)/(x+3)


(x+3)/(x-3)\cdot \left[(2\cdot (x+3)-4\cdot x)/(x+3) \right] = 7


(2\cdot (x+3)-4\cdot x)/(x-3) = 7


2\cdot (x+3) -4\cdot x = 7\cdot (x-3)


2\cdot x + 6 - 4\cdot x = 7\cdot x -21


2\cdot x - 4\cdot x -7\cdot x = -21-6


-9\cdot x = -27


x = 3

User Whypee
by
4.5k points